Associação temporal da terapia endócrina com tamoxifeno e da quimioterapia sobre o risco nutricional e obesidade em pacientes com câncer de mama - Lima, Mariana Tavares Miranda (2017)
Background: Although still controversial, breast cancer (BC) patients may present anthropometric changes as well as changes in body composition during the period of endocrine therapy with tamoxifen (TMX). However, previous treatments, such as chemotherapy (CT), also stand out in this process. In this sense, it is relevant to study the anthropometric and body composition changes in different moments of endocrine therapy with TMX and its associations with CT. Objectives: To verify the influence over time of endocrine therapy with TMX on nutritional risk and obesity and its association with CT in patients with BC. Material and methods: Cross-sectional study carried out in 2015-2016 with 84 women with BC in endocrine therapy with TMX and categorized into three groups according to the duration of medication use. Anthropometric, biochemical and body composition parameters were analyzed. The generalized estimation equation (GEE) was used to examine the association between CT and the groups of TMX duration use, adjusting for confounding factors. Results: Women who received CT just prior to the start of endocrine therapy (group 1), when compared to those who did not within the same group, showed significantly higher values for Body Mass Index (BMI) (29.14 ± 0.93; 25.29 ± 0.46 Kg/m2, p=0.003, respectively), waist circumference (WC) (94.45 ± 1.96; 85.84 ± 0.90 cm, p=0.001, respectively) and percentage of body fat (%BF) (36.36 ± 1.50; 30.32 ± 0.43 %, p=0.001, respectively). In contrast, in the group of women who did not have CT, when we compared group 1 and group 2, we observed lower values of BMI (25.29 ± 0.46; 28.40 ± 0.95 kg/m2, p=0.042, respectively), WC (85.84 ± 0.90; 97.75 ± 0.88 cm, p=0.000, respectively) and %BF (30.32 ± 0.43; 42.95 ± 1.03 %, p=0.000, respectively). Also, in group 2, higher values of WC were observed in relation to group 3 (97.75 ± 0.88; 76.00 ± 7.03 cm, respectively, p=0.025).Conclusion: Women on endocrine therapy with TMX are mostly overweight and obese and this was most evident in women who received CT and who were at the beginning of treatment. Women who did not have CT, despite presenting lower values of BMI, WC and %BF in group 1, deserve special attention because a significant increase in the values evaluated was verified when compared with group 2.